2022
DOI: 10.1101/2022.10.05.508277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-omic Analysis of Primary Human Kidney Tissues Identifies Medulla-Specific Gene Expression Patterns

Abstract: The renal medulla is a specialized region of the kidney with important homeostatic functions. It has also been implicated in genetic and developmental disorders and ischemic and drug-induced injuries. Despite its role in kidney function and disease, the medulla's baseline gene expression and epigenomic signatures have not been well described in the adult human kidney. Here we generate and analyze gene expression (RNA-seq), chromatin accessibility (ATAC-seq) and chromatin conformation (Hi-C) data from adult hum… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The factors that control these changes are not fully understood. There is plenty of evidence that the unique hypertonic environment in the renal inner medulla mediates a specific gene expression pattern 12, 29, 52 31 . With this study, we provide evidences that the differences in the chromatin accessibility contribute to the observed changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The factors that control these changes are not fully understood. There is plenty of evidence that the unique hypertonic environment in the renal inner medulla mediates a specific gene expression pattern 12, 29, 52 31 . With this study, we provide evidences that the differences in the chromatin accessibility contribute to the observed changes.…”
Section: Discussionmentioning
confidence: 99%
“…This data indicates that the enriched Aqp2 expression in the IM is associated with increased accessibility at the TSS and that probably hypertonicity induces the observed differences. Recently, Haug et al analysed chromatin accessibility and spatial transcription in the adult human kidney cortex and medulla 31 . Haug et al identified around 2,300 differentially expressed genes between renal cortex and renal medulla.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These investigators examined both glomerular and tubulointerstitial ROIs and found that antibody-mediated rejection was more pronounced in glomeruli with influx of monocytes, macrophages, and natural killer cells. Finally, we have recently shown that spatial profiling can be used to validate findings from other -omics technologies in place of traditional techniques such as immunohistochemistry [ 55 ].…”
Section: Insights Into Kidney Disease Gleaned From Spatial Transcript...mentioning
confidence: 99%